The conceptualisation, institutionalisation, delivery and management of public space in the Buffalo City Metropolitan Municipality : towards integrated placemaking and greening practices - Landman, Karina (University of Pretoria, 2023)
Thesis (PhD (Town and Regional Planning))--University of Pretoria, 2021.